1989
DOI: 10.1073/pnas.86.9.3189
|View full text |Cite
|
Sign up to set email alerts
|

Gene for proliferating-cell nuclear antigen (DNA polymerase delta auxiliary protein) is present in both mammalian and higher plant genomes.

Abstract: Proliferating-cell nuclear antigen (PCNA; also called cyclin) was originally described in proliferating mammalian cells as a nuclear protein with an apparent Mr of 33,000-36,000 and recently was found to be a DNA polymerase 6 auxiliary protein.To elucidate whether PCNA/cyclin is a universal protein necessary for proliferation of eukaryotes, a search was conducted for PCNA/cyclin homologues in higher plants. In Southern blot-hybridization analysis, a rat PCNA/ cyclin cDNA probe hybridized with homologous sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
6

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 26 publications
1
56
1
6
Order By: Relevance
“…We have isolated and characterized both genomic clones and cDNAs for plant proliferating cell nuclear antigen (PCNA, an auxiliary protein of DNA polymerase 6; this should not be confused with cyclins (Suzuka et al, 1989(Suzuka et al, , 1991. It has also been reported that plants have p34cdc2 or related proteins (John et al, 1989;Feiler and Jacobs, 1990;Hata, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…We have isolated and characterized both genomic clones and cDNAs for plant proliferating cell nuclear antigen (PCNA, an auxiliary protein of DNA polymerase 6; this should not be confused with cyclins (Suzuka et al, 1989(Suzuka et al, , 1991. It has also been reported that plants have p34cdc2 or related proteins (John et al, 1989;Feiler and Jacobs, 1990;Hata, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequences of proliferating cell nuclear antigen (PCNA) present high homology among mammalians, and also in superior vegetal (28) . In our cases, nuclear reactivity for PCNA was strong, with faint cytoplasmic staining in mitotic cells (12,34) .…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is an essential protein, highly conserved in all eukaryotes, including plants (Suzuka et al 1989;Kodama et al 1991;Hata et al 1992;Matsumoto et al 1994;Lopez et al 1995;Shimizu and Mori 1998;Strzalka et al 2010). It is frequent that plant genomes contain two PCNA genes, in contrast to PCNA pseudogenes normally found in mammalian cells.…”
Section: Pcnamentioning
confidence: 99%